Fundo Comarca de Santa Maria (1910 - 1946): A digitalização como auxílio ao acesso e a preservação do patrimônio documental - Nunes, Janilton Fernandes (2014)
The present dissertation research has as the analysis of procedures for document preservation, such as the description, the scanning, and the availability of digital representative on the internet, of ciminal case of fonds Judicial District of Santa Maria (JDSM), corresponding to the period 1910-1946 . Currently, this documentary fonds is in the custody of the Municipal Historical Archive of the City of Santa Maria (AHMSM). The research aims to decrease the handling of original documents, thus contributing to the preservation of documentary heritage. Create a finding aid that allows quick access to contents of the fonds Judicial District of Santa Maria. The fonds framed in the classification scheme of the AHMSM and is considered closed, organized chronologically. The related documents are composed of 604 stored procedures in 70 standard file boxes totaling 77,000 images. This work proceeded research, creation and review of the descriptions of each process fonds. This work, necessary for the preparation and launch of data in the archival description ICA-AtoM software. The fonds scanning was performed, permeated with the standards and recommendations mainly the National Council on Archives of Brazil (CONARQ), which passed the feasibility study of equipment and the creation of digital documents representative of the fonds. The AHMSM today have digital representatives of the Judicial District of Santa Maria fonds available, with access via the Internet. The consolidation of JDSM, replicated in digital format, adds another responsibility to AHMSM, which is responsible for the maintenance and access the content on the other hand, the body receives a finding aid, the catalog, which reduces the handling of original documents, enabling fast access to content.